Comparative Feasibility Analysis of Mechanized Equipment for Vineyard Operations - Guilherme Signorini; Melanie L. Lewis Ivey (HortTechnology, 2023)
Increasing labor and input costs have driven wine grape (Vitis vinifera) growers’ attention to mechanized equipment to assist in vineyard operations. This study evaluates the financial feasibility of investing in vineyard mechanization, in addition to the released intelligent sprayer in hypothetical wine grape vineyards of varying sizes. Our comparative analysis illustrates how mechanization of vineyard practices affects costs and financial metrics. We conducted a cost–benefit analysis for seven investment scenarios and examined the economic performance of four metrics. Our findings suggest that investing in a mechanized trimmer is most effective for growers exposed to labor shortages and high wages. A retrofitted intelligent sprayer is superior for reducing input use and associated costs.